Incentives and Competition in the Airline Industry - Aggarwal, Rajesh K; Schenone, Carola (The Review of Corporate Finance Studies, 2019)
Abstract We examine how performance changes at airlines in response to a change in executive incentives. Airlines with executive bonuses contingent on on-time arrival do improve on-time performance. We find evidence of strategic gaming of the incentive as some carriers increase scheduled flight times, making it easier for flights to arrive on time. This effect is more pronounced for competitive routes. Carriers also do not decrease the frequency of flights or the number of passengers to make it easier to be on time, but they do slightly decrease fares. Competitors on the same routes also improve their on-time performance, even when their executive bonuses are not contingent on on-time performance, consistent with competition in strategic complements. (JEL G30, G34, G32) Received February 5, 2018; editorial decision April 3, 2019 by Editor Andrew Ellul.